Systemic Targeted Alpha Radiotherapy for Cancer - A Review (Bangladesh Journal of Medical Physics, 2014)
The fundamental principles of internal targeted alpha therapy for cancer were established many decades ago. The high linear energy transfer (LET) of alpha radiation to the targeted cancer cells causes double strand breaks in DNA. At the same time, the short range of alpha- radiation spares adjacent normal tissues. This targeted approach complements conventional external beam radiotherapy and chemotherapy. Such therapies fail on several fronts, such as lack of control of some primary cancers (eg glioblastoma multiforme) and inhibition of the development of lethal metastatic cancer after successful treatment of the primary cancer. This review charts the developing role of systemic high LET in internal radiation therapy. Targeted alpha therapy is a rapidly advancing experimental therapy that holds promise to deliver high cytotoxicity to targeted cancer cells. Initially thought to be indicated for leukaemia and micrometastases, there is now evidence that solid tumours can also be regressed. Alpha therapy may be molecular or physiological in its targeting. Alpha emitting radioisotopes such as Bi-212, Bi-213, At-211 and Ac-225 are used to label monoclonal antibodies or proteins that target specific cancer cells. Alternatively, radium-233 is used for palliative therapy of breast and prostate cancers because of its bone seeking properties. In this review, preclinical studies and clinical trials of alpha therapy are discussed for leukaemia, lymphoma, melanoma, glioblastoma multiforme, bone metastases, ovarian cancer, pancreatic cancer and other cancers.   DOI: http://dx.doi.org/10.3329/bjmp.v6i1.19755 Bangladesh Journal of Medical Physics Vol.6 No.1 2013 21-38